Leadership in Action : Face to Face - Quality Leadership - A Conversation with Dennis R. Barry - Patterson, Editor Tracy (Center for Creative Leadership, 2006)
Barry recently spoke with David Altman, vice president of research and innovation at CCL, and Tracy Patterson, a research and innovation associate at CCL, about the current challenges facing leaders in the health care field. Here are excerpts from that interview